Phytochemical and Cytotoxic Test of Durio kutejensis Root Bark on MCF-7 Cells - Muhammad Priyadi; Haryoto Haryoto; Amaliyah Dina Anggraeni; Heng Yen Khong (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Durio kutejensis has known potential as herbal medicine in Kalimantan. Many things can be explored from D. kutejensis related pharmacological activity in every part of the plant included root bark. This study investigated the phytochemical content with a qualitative test and tested cytotoxic activities of D. kutejensis root bark on MCF-7 cell lines. Cytotoxic activity tested on MCF-7 cells with MTT assay method. The result showed that D. kutejensis root bark contains flavonoid, tannin, terpenoid, phenol, and saponin. IC50 value for ethanol extracts of root bark, n-hexane fractions, ethyl acetate fractions, and doxorubicin on MCF-7 cells were 761.29; 280.5; 207.08; and 0.25 μg/mL, respectively. In conclusion, D. kutejensis root bark has some secondary metabolites but no cytotoxic activity on MCF-7 cells. Further research is needed to explore the anticancer activity of secondary metabolites on some other cancer cells and other pharmacological activities.